Arbuscular Mycorrhizal Fungi (Glomus mosseae) Improves Growth, Photosynthesis and Protects Photosystem II in Leaves of Lolium perenne L. in Cadmium Contaminated Soil - Zhang, Huihui; Xu, Nan; Li, Xin; Long, Jinghong; Sui, Xin; Wu, Yining; Li, Jinbo; Wang, Jifeng; Zhong, Haixiu; Sun, Guang Y. (Frontiers in Plant Science, 2018)
The effects of inoculating arbuscular mycorrhizal fungi (Glomus mosseae) on the growth, chlorophyll content, photosynthetic gas exchange parameters and chlorophyll fluorescence characteristics of Lolium perenne L. in cadmium (Cd) contaminated soil were investigated in this research. The results showed that the root vigor of L. perenne in cadmium contaminated soil declined, and the chlorophyll content significantly decreased with the increase of Cd content, especially the chlorophyll a content of leaves. The photosynthetic carbon assimilation capacity and PS II activity of L. perenne leaves were also significantly inhibited by Cd stress, especially electron transfer at the receptor side of PSII, which was more sensitive to Cd stress. The infection level of G. mosseae on L. perenne roots was relatively high, and inoculation with G. mosseae could make the mycorrhizal infection rate of L. perenne roots reach up to 50%–70%. Due to the impact of the mycorrhizal infection, root vigor of L. perenne increased to some extent, and it alleviated the chlorophyll degradation in L. perenne leaves under cadmium contaminated soil. Infection with G. mosseae can improve the stoma limitation of L. perenne L. leaves in Cd contaminated soil, and also increase the non-stomatal factors including the tolerance of its photosynthetic apparatus to Cd, in order to improve the photosynthetic capacity. Glomus mosseae infection can improve the photosynthetic electron transport capacity of PSII in L. perenne leaves under Cd stress, and has different degrees of promoting effects on the activity of the oxygen-evolving complex (OEC) at the donor side of PSII and the electron transport capacity from QA to QB on the receptor side of PSII. Thus, this acts to guarantee that L. perenne leaves inoculated with G. mosseae in Cd contaminated soil has relatively higher PSII activity. Therefore, inoculation with G. mosseae can improve the capacity of Cd tolerance of L. perenne from various aspects, such as morphological characteristics and photosynthetic functions, and reduce the toxicity of Cd on Lolium perenne.